Improvement of students problem-solving skills through project execution planning in civil engineering and construction management education. Issue 7 (10th July 2019) - Zhang, Jingxiao; Xie, Haiyan; Li, Hui
Abstract : Purpose: The purpose of this paper is to improve students' problem-solving skills in civil engineering and construction management education. Design/methodology/approach: The design includes structured role-playing as a pedagogical method in 21 project teams with a total of 82 undergraduate students at Chang'an University, China, in a nine-week Building Information Modeling (BIM) capstone course. The methodology is a teaching–learning experiment in a civil engineering education program with a detailed description of the empirical case and assessment instruments. The approach is to train project execution planning in a capstone course by role-playing with a real-world project using the procedures of the BIM Project Execution Planning Guide (PEPG) and process mapping. Findings: The study finds that students can significantly improve their problem-solving skills through planning and role-specific communication during projects. Research limitations/implications: The research sample needs to be expanded from senior-level undergraduate students to consider the different backgrounds and motivations of students. Practical implications: This pedagogy is helpful to educators who are interested in group learning with a real-world project; the procedures of BIM PEPG; self-chosen responsibilities within a capstone course time framework; raising the awareness of the importance of planning; information exchange; and team cooperation. Originality/value: This paper fulfills an identified need to study how role-playing in information and technology rich environments can be structured.